Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

the expression (3x^2)^4/9x^3 is equivalent to which other expression

Sagot :

[tex]\frac{(3x^2)^4}{9x^3}=\frac{3^4x^{2\cdot4}}{9x^3}=\frac{81x^8}{9x^3}=9x^{8-3}=9x^5[/tex]